Environment Conservation in Pressing Climate Change Environmental Fiqih and Islamic Law - Abdurohim, Abdurohim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The world's climatic conditions are increasingly concerning due to pollution from household waste to industrial waste which causes acid rain, climate change, ozone layer erosion, water, air, and soil quality must be considered so as not to cause harm to humans and other living things. Environmental preservation makes it a burden for humans as subjects to maintain environmental sustainability which is getting worse and weak supervision and law enforcement also affect the decline in water, soil, and air quality. This research was conducted to demonstrate the strategic role of humans in controlling water, air, and soil pollution as well as preventing climate change in issuing permits, monitoring, imposing sanctions, and efforts to overcome those that cause a spike in greenhouse gasses.